2010
DOI: 10.1099/mic.0.033621-0
|View full text |Cite
|
Sign up to set email alerts
|

A distinct physiological role of MutY in mutation prevention in mycobacteria

Abstract: Oxidative damage to DNA results in the occurrence of 7,8-dihydro-8-oxoguanine (8-oxoG) in the genome. In eubacteria, repair of such damage is initiated by two major base-excision repair enzymes, MutM and MutY. We generated a MutY-deficient strain of Mycobacterium smegmatis to investigate the role of this enzyme in DNA repair. The MutY deficiency in M. smegmatis did not result in either a noteworthy susceptibility to oxidative stress or an increase in the mutation rate. However, rifampicin-resistant isolates o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
1
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 33 publications
4
30
1
3
Order By: Relevance
“…However, under oxidative stress conditions, generated by supplementation of cultures with H 2 O 2 , loss of MutY results in a significant decline in growth compared to the parental strain which is not exaggerated with the combinatorial loss of the Fpg or Nei homologues, suggesting that MutY is important for survival of M. smegmatis under oxidative stress conditions. These data are concordant with the loss of MutY function in M. tuberculosis [39], but conflict with a previous report which demonstrated that disruption of mutY in M. smegmatis does not lead to enhanced sensitivity to hydrogen peroxide [22]. In our work, we used the same parental strain of M. smegmatis [56] with similar experimental conditions hence, the reason for these discrepant results are unclear and may be due to the inherent variability in mutant generation, difference in quantitative survival assays or hydrogen peroxide decay.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…However, under oxidative stress conditions, generated by supplementation of cultures with H 2 O 2 , loss of MutY results in a significant decline in growth compared to the parental strain which is not exaggerated with the combinatorial loss of the Fpg or Nei homologues, suggesting that MutY is important for survival of M. smegmatis under oxidative stress conditions. These data are concordant with the loss of MutY function in M. tuberculosis [39], but conflict with a previous report which demonstrated that disruption of mutY in M. smegmatis does not lead to enhanced sensitivity to hydrogen peroxide [22]. In our work, we used the same parental strain of M. smegmatis [56] with similar experimental conditions hence, the reason for these discrepant results are unclear and may be due to the inherent variability in mutant generation, difference in quantitative survival assays or hydrogen peroxide decay.…”
Section: Discussionsupporting
confidence: 76%
“…The reduced frequency of the remaining mutations detected did not allow for meaningful comparisons to be made. Loss of Fpg and MutY function is expected to exacerbate G·C→T·A transversion mutagenesis due to persisting 8-oxoGua lesions that mispair with adenine [21,22]. Consistent with this, the Rif-resistant isolates derived from the fpg1 fpg2 mutY mutant showed approximately a 30-45% increase in the C → A (Gln513 → Lys) mutational genotype compared to the single mutY and the double fpg1 fpg2 deletion mutants respectively.…”
Section: Strainmentioning
confidence: 54%
See 3 more Smart Citations